2010
DOI: 10.1111/j.1365-2133.2010.09892.x
|View full text |Cite
|
Sign up to set email alerts
|

History of eczema herpeticum is associated with the inability to induce human β-defensin (HBD)-2, HBD-3 and cathelicidin in the skin of patients with atopic dermatitis

Abstract: KeywordsADEH; AMPs MADAM, Patients with atopic dermatitis (AD) with a history of eczema herpeticum (ADEH) represent a subset of individuals with AD who have more severe disease. 1 It has previously been shown that the skin of patients with AD has defects in its capacity to increase maximally the antimicrobial peptides (AMPs), cathelicidin, human β-defensin (HBD)-2 and HBD-3 in response to inflammation, in contrast to patients with psoriasis who also have inflammation of the skin, but no difficulty with AMP ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 6 publications
2
49
1
2
Order By: Relevance
“…Other studies which focused on hBD-3, and dermcidin, an AMP found in sweat glands, supported these observations (81, 82). Decreased LL-37, hBD-2 and hBD-3 have also been reported in the skin of AD patients colonized by herpes simplex virus compared with non-colonized patients (83, 84). …”
Section: Barrier Defects and The Epidermismentioning
confidence: 86%
“…Other studies which focused on hBD-3, and dermcidin, an AMP found in sweat glands, supported these observations (81, 82). Decreased LL-37, hBD-2 and hBD-3 have also been reported in the skin of AD patients colonized by herpes simplex virus compared with non-colonized patients (83, 84). …”
Section: Barrier Defects and The Epidermismentioning
confidence: 86%
“…Dysfunctional induction of cathelicidin has been demonstrated in injured lesional skin in AD in another study, which could contribute to the increased susceptibility of AD patients to skin infections [35]. Clinical and experimental data support the view that AD patients with a history of eczema herpeticum show a defective upregulation of AMP [32,36].…”
Section: Antimicrobial Peptidesmentioning
confidence: 92%
“…This suggests that epidermal barrier defects such as the loss-of-function mutations found within the filaggrin gene ( FLG ) (Bisgaard et al, 2008; Palmer et al, 2006; Sandilands et al, 2007; Smith et al, 2006) could promote disease. In addition, the epidermis of AD subjects can have a decreased capacity to produce AMPs such as cathelicidin and β-defensins (Hata et al, 2010; Howell et al, 2006a; Howell et al, 2006b; Mallbris et al, 2010; Ong et al, 2002). Such antimicrobial or physical barrier defects may facilitate physical penetration of the epidermis by bacteria that otherwise would not trigger inflammation on normal skin.…”
Section: Introductionmentioning
confidence: 99%